Homophily in Personality Enhances Group Success Among Real-Life Friends - Laakasuo, Michael; Rotkirch, Anna; van Duijn, Max; Berg, Venla; Jokela, Markus; David-Barrett, Tamas; Miettinen, Anneli; Pearce, Eiluned; Dunbar, Robin (Frontiers in Psychology, 2020)
Personality affects dyadic relations and teamwork, yet its role among groups of friends has been little explored. We examine for the first time whether similarity in personality enhances the effectiveness of real-life friendship groups. Using data from a longitudinal study of a European fraternity (10 male and 15 female groups), we investigate how individual Big Five personality traits were associated with group formation and whether personality homophily related to how successful the groups were over one year (N=147–196). Group success was measured as group performance (adoption of group markers) and as group bonding (using the inclusion-of-other-in-self scale). Results show that individuals’ similarity in neuroticism and conscientiousness predicted group formation. Furthermore, personality similarity was associated with group success, after controlling for individual variation in personality. Especially higher group-level similarity in conscientiousness was associated with group performance, and with bonding in male groups.